Lamina propria group 2 innate lymphoid cells impair the antibacterial defense of burned mice to enterococcal translocation. Issue 6 (26th September 2017) - Ito, Ichiaki; Bhopale, Kamlesh K; Kobayashi, Makiko; Finnerty, Celeste C; Herndon, David N; Suzuki, Fujio
Abstract : Improved antibacterial resistance in severely burned mice treated with SR3335, an inhibitor of ILC2. Abstract: Gut microbiota that invades to the defective mucosal barrier is one of the major sources of infectious complications in severely burned hosts. In this study, a role of group 2 innate lymphoid cells (ILC2) and effects of N -{4-[2, 2, 2-trifluoro-1-hydroxy-1-(trifluoromethyl)ethyl]phenyl}-2-thiophenesulfonamide (SR3335) on the host antibacterial resistance against infectious complications caused by Enterococcus faecalis oral infection were investigated in burned mice. Retinoic acid receptor-related orphan receptor α (RORα) is a transcription factor required for the development of ILC2, and SR3335 is an RORα-selective inverse agonist. All of burned mice died within 6 d of E. faecalis infection (5 × 10 6 CFU/mouse), whereas 100% of the same mice treated with SR3335 survived. The increased ILC2 and their cytokine products (IL-5 and IL-13) were detected in the lamina propria of mice, 1–7 d after burn injury. However, the number of ILC2 did not increase in the lamina propria of burned mice treated with SR3335. The antibacterial resistance of SCID-beige (SCIDbg) mice to E. faecalis infection was impaired by the inoculation of ILC2. BALB/c, SCIDbg, and polymorphonuclear leukocyte (PMN)-depleted SCIDbg mice were shown to be resistant against E. faecalis infection. However, all Mϕ depleted SCIDbg mice died after the infection. These results indicate that host antibacterial effector Mϕ against enterococcal translocation are influenced by ILC2, increased in the bacterial translocation site of burned mice, and sepsis stemming from E. faecalis oral infection was amazingly mitigated in these mice after treatment with SR3335, an inhibitor of cellular differentiation from an ILC precursor (ILCP) to ILC2.